A bricolage of identifications: storying postmigrant belonging. Issue 2 (21st August 2017) - Bromley, Roger
ABSTRACT: How, and at what point, does a person, or a group of people, described as migrant or of migrant origin, cease to be thought of as migrants or exclusively in terms of their ethnicity? This article responds to this question by exploring a range of theoretical arguments in relation to what has come to be called postmigration. The emphasis is on second and third generation "migrants", born in their country of residence, and on the ways in which through developing new cultural and representational practices they seek to go beyond confining and essentialising definitions which have an "othering" effect. At the same time, it is acknowledged that those of the first generation may also be engaged in a similar struggle to find agency in forms of the future. In speculating on possible meanings of postmigration, two texts will be examined, one a work of fiction, the other a social and cultural survey, which implicitly or explicitly address ways of transcending the limits of minority ascription in the context of racism, xenophobia, traditionalism, and Islamophobia.